ANALISA MIKROBIOLOGI DAN ORGANOLEPTIK PRODUK TENGGIRI BEKU(Scomberomorus commersonii) - Mulyana, Mulyana; Yanti, Dwi Indah Widya (Sam Ratulangi University, 2018)
Mackerel fish is sea fishs species which are pelagic marine fish groupwhich has a distinctive taste so favored by the people. frozen mackerel is a fishs that is easily damaged. Thus the fishs need to be handling it well. Fishskeep the temperature will affect the quality of the fishs. during storage in the storage and distribution processing. can affect product quality. To decrease the quality of frozen mackerel fishs products need to note the changes that occur either through physical, chemical and biological. It explains research to analyze the quality of fishs products frozen mackerel observe Â aspects of Microbiology testing and Appearance. Based on the results of microbiological and organoleptic frozen mackerel fish, it can be conclude that test for microbiological test total plate count (TPC) is below the standard value in accordance with ISO 4110, 2014. for Uju E, coli is negative, Salmonella Test is Begatif, Vibrio Colera test is also negative and Appearance Test Values above 7 quality fish so the test results of Microbiology and poduct organoleptic frozen mackerel safe for consumption as the above test result.